2011
DOI: 10.3109/01443615.2010.538773
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with psychological morbidity in mothers of pre-term infants: A study from Wesley Guild Hospital, Nigeria

Abstract: This was a cross-sectional prospective study of 57 mothers of pre-term infants consecutively recruited from the Neonatal Intensive Care Unit (NICU) of Wesley Guild Hospital, Ilesa, Nigeria, between April and August 2009. The mothers were screened for psychological morbidity using the General Health Questionnaire (GHQ-30), and the Hospital Anxiety and Depression Inventory (HADS). More than one-third of these mothers (36.8%), showed high levels of psychological distress on the GHQ30, and 19.3% were cases of depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, having a child prematurely "violates a mother's cognitive schema" (Greene et al, 2015, p. 369); the mental representation of what motherhood is expected to be is disrupted due to the truncating of the pregnancy and subsequent feelings of loss, grief, and anxiety (Woodward et al, 2014) associated with preterm birth. Low (<2,500g), very low (<1,500g), or extremely low (<1,000g) birth weight of the infant have been shown to affect parental development of mood and anxiety disorders in several studies (Al-Akour et al, 2014;Chang et al, 2016;Greene et al, 2015;Helle et al, 2016;Ukpong, 2011). Gestational age at birth correlates with an increase in PPD and anxiety symptoms in mothers of infants hospitalized in the NICU (Al-Akour et al, 2014;Chang et al, 2016;Kong et al, 2013;Misund et al, 2014;Ukpong, 2011); however, one study did not find significant correlations between infant gestational age and scores on the psychometric tools utilized to assess parent psychological functioning (Busse et al, 2013).…”
Section: Intrapersonal Levelmentioning
confidence: 99%
“…Furthermore, having a child prematurely "violates a mother's cognitive schema" (Greene et al, 2015, p. 369); the mental representation of what motherhood is expected to be is disrupted due to the truncating of the pregnancy and subsequent feelings of loss, grief, and anxiety (Woodward et al, 2014) associated with preterm birth. Low (<2,500g), very low (<1,500g), or extremely low (<1,000g) birth weight of the infant have been shown to affect parental development of mood and anxiety disorders in several studies (Al-Akour et al, 2014;Chang et al, 2016;Greene et al, 2015;Helle et al, 2016;Ukpong, 2011). Gestational age at birth correlates with an increase in PPD and anxiety symptoms in mothers of infants hospitalized in the NICU (Al-Akour et al, 2014;Chang et al, 2016;Kong et al, 2013;Misund et al, 2014;Ukpong, 2011); however, one study did not find significant correlations between infant gestational age and scores on the psychometric tools utilized to assess parent psychological functioning (Busse et al, 2013).…”
Section: Intrapersonal Levelmentioning
confidence: 99%
“…Researchers reported that parents with an infant admitted to the NICU experienced feelings of anxiety, depression, stress, and distress Doering et al, 2000;Dudek-Shriber, 2004;Ukpong, 2011). Anxiety, depression, and distress are concepts studied concurrently with stress.…”
Section: Chapter II Review Of the Literaturementioning
confidence: 99%
“…Anxiety, depression, and distress are concepts studied concurrently with stress. Mothers of preterm infants (N = 57) during NICU hospitalization reported high levels of psychological distress (36.8%), depressive symptoms (19.3%), and anxiety (12.3%) related to their infant's low birth weight and low gestational age (Ukpong, 2011).…”
Section: Chapter II Review Of the Literaturementioning
confidence: 99%